2002
DOI: 10.1083/jcb.200112126
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interaction of VCAM-1 and ICAM-1 with moesin and ezrin in a novel endothelial docking structure for adherent leukocytes

Abstract: Ezrin, radixin, and moesin (ERM) regulate cortical morphogenesis and cell adhesion by connecting membrane adhesion receptors to the actin-based cytoskeleton. We have studied the interaction of moesin and ezrin with the vascular cell adhesion molecule (VCAM)-1 during leukocyte adhesion and transendothelial migration (TEM). VCAM-1 interacted directly with moesin and ezrin in vitro, and all of these molecules colocalized at the apical surface of endothelium. Dynamic assessment of this interaction in living cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
569
2
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(600 citation statements)
references
References 56 publications
26
569
2
3
Order By: Relevance
“…Although neither fibronectin [27], [33] nor VCAM-1 [18] is required for implantation, CD49d expression on trophoblast might be able to make use of VCAM-1, were it cyclically expressed in mouse as it is in human maternal decidua [10]. Such interaction may make use of ezrin/radixin/moesin (ERM) proteins crosslinking actin filaments with plasma membranes [34]. The resulting signal transduction could facilitate trophectoderm invasion and further embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Although neither fibronectin [27], [33] nor VCAM-1 [18] is required for implantation, CD49d expression on trophoblast might be able to make use of VCAM-1, were it cyclically expressed in mouse as it is in human maternal decidua [10]. Such interaction may make use of ezrin/radixin/moesin (ERM) proteins crosslinking actin filaments with plasma membranes [34]. The resulting signal transduction could facilitate trophectoderm invasion and further embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…These endothelial structures were first described by Barreiro and colleagues who defined them as docking structures. 66 Other researchers found similar endothelial structures but proposed different names, e.g. transmigratory cups, apical cups, dome structures, ICAM-1-enriched contact areas, or actin dynamic structures.…”
Section: Paracellular and Transcellular Migrationmentioning
confidence: 98%
“…ICAM-1 has also been known to be associated with ezrin/radixin/moesin (ERM) family members, i.e., ezrin and moesin (Heiska et al, 1998;Barreiro et al, 2002). To test whether truncation of the intracellular domain alters the association of ICAM-1 with the proteins mentioned above, the subcellular distribution of ICAM-1, actin, ezrin, and moesin was analyzed by confocal microscopy in COS-7 cells transfected with wt-IC1_GFP or IC1⌬CTD_GFP.…”
Section: The Distribution and Dynamic Movements Of Icam-1 On Transfecmentioning
confidence: 99%
“…Recent reports have demonstrated that ICAM-1/LFA-1 or VCAM-1/VLA-4 interactions promote formation of endothelial projections that surround adherent lymphocytes and are enriched in ICAM-1, VCAM-1, ezrin, and actin (Barreiro et al, 2002;Carman et al, 2003). High-resolution imaging study has also suggested that this structure may function to facilitate and guide TEM by forming a cuplike traction structure called a "transmigratory cup" that is aligned parallel to the direction of transmigration (Carman and Springer, 2004).…”
Section: Introductionmentioning
confidence: 99%